HUBUNGAN PUASA DAN TINGKAT REGULASI KEMARAHAN - Very Julianto; Pipih Muhopila (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
The research aimed to understand the relation between fasting and the anger regulation. Subject’s researchs were 100 students of UIN Sunan Gunung Djati Bandung taken by random sampling. Subjects consist of 43 man and 57 woman. This research used quantitative method. Data was collected by questionare, and method of analysis was Pearson’s correlation test. The result has shown there is relation between fasting and the anger regulation with scale of correlation was 54%. Subject that often fasting, carbohydrate input was lower so that the subject had high level of anger regulation.